[A Tunnel of Trees] - (:unkn) unknown (My University, 2009)
A picture of trees lining a road with its thick foliage entangled overhead creating a tunnel.
Colour; Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trees; Roads